INOVASI FERMENTASI PUCUK TEBU UNTUK EFISIENSI PAKAN HIJAUAN KAMBING PERAH PADA KELOMPOK TANI MUDA MANDIRI KECAMATAN SUNGAI PUA KABUPATEN AGAM - Pazla, Roni; Sri Suharto, El Latifa; Welan, Rahmani; Antonius, Antonius; Yanti, Gusri; Hidayat, Muhammad Zhorif; Purnomo, Vito Dwi; Romadhon, Rizki; Ikhlas, Zaitul; Haq, Naufal Al (LPPM (Lembaga Penelitian dan Pengabdian kepada Masyarakat) Universitas Andalas, 2024)
The dairy goat farming business is quite developed in Agam Regency, one of which is the Muda Mandiri farmer group in Nagari Sungai Pua, Sungai Pua District. This group has 11 members of peranakan etawa goat breeders with 30 goats. The purpose of this activity is to apply sugarcane tops fermentation technology as an alternative forage feed for ruminants to improve the feed efficiency of dairy goats. The activity method includes several stages. Fisrt, concept introduction and counselling to farmer groups on forage feed management and the benefits of sugarcane tops fermentation were conducted. Second, a demonstration of the fermentation process began with chopping sugarcane tops, mixing them with Pleurotus ostreatus mold and adding bran. This mixture was stored in an airtight container for 21 days. Third, the fermented products were tested directly as feed for dairy goats to evaluate their palatability and impact on milk production. Important results showed that although milk production was almost the same as the previous feed of field grass, fermented sugarcane tops could replace up to 30% of field grass use. This reduced the need for farmers to search for grass every day, improving time and labor efficiency in feed preparation. In conclusion, fermented sugarcane tops is an effective and easy-to-implement technology to support the provision of efficient alternative feed for dairy goat farmers, thereby helping to ease the farmer’s workload.